Interleukin (IL)‐6 modulates transforming growth factor‐β receptor I and II (TGF‐βRI and II) function in epidermal keratinocytes. Issue 8 (8th March 2017) - Luckett‐Chastain, Lerin R.; Cottrell, Mackenzie L.; Kawar, Bethany M.; Ihnat, Michael A.; Gallucci, Randle M.
Abstract: It been shown that IL‐6 modulates TGF‐β1 expression in fibroblasts, however, what role IL‐6 plays concerning TGF‐βR expression and function in skin is unknown. Therefore, the aim of this study was to investigate the mechanism by which IL‐6 might modulates TGF‐β receptors in skin. Skin from WT, IL‐6 over‐expressing mice and IL‐6 treated keratinocyte cultures was analysed for TGF‐βRI and TGF‐βRII expression via histology, PCR and flow cytometry. Receptor function was assessed by cell migration, bromodeoxyuridine (BrdU) proliferation assays, and Smad7 expression and Smad2/3 phosphorylation. Receptor localization within the membrane was determined by co‐immunoprecipitation. IL‐6 overexpression and treatment increased TGF‐βRII expression in the epidermis. IL‐6 treatment of keratinocytes induced TGF‐βRI and II expression and augmented TGF‐β1‐induced function as demonstrated through increased migration and decreased proliferation. Additionally, IL‐6 treatment of keratinocytes altered receptor activity as indicated by altered Smad2/3 phosphorylation and increased Smad7 and membrane localization. These results suggest that IL‐6 regulates keratinocyte function by modulating TGF‐βRI and II expression and signal transduction via trafficking of the receptor to lipid raft pools.